Granit, sandsten, kalksten og klæbersten. Danske romanske døbefonte på rejse - Ebbe Nyborg (ICO Iconographisk Post, 2018)
Title in English: Granite, Sandstone, Limestone and Soapstone. Danish Romanesque Baptismal Fonts and their Travels